Comparative study of fiberglass-reinforced pipe for oil and gas processing industries based on fire and explosion risk analysis - Mansor, Zulkfley (2001)
In this paper the suitability of fiberglass-reinforced pipe (FRP) for Lise in oil and gas processing industries fire fighting system was studied The study covered the issues on the reliability as well as the cost benefit that could be obtained from the FRP material as compared to conventional metallic materials commonly used in the said system. In addition, a discussion on the recent test results on FRP material concerning its mechanical and thermal properties, fire resistance, corrosion resistance, cost benefits and consequently approval status by the International Regulatory and Classification Societies are also presented in this paper for evaluation of its suitability The results of the study show that the FRP pipes are suitable for oil and gas processing industries fire fighting system provided that the "blowdown" system and the firewater deluge system are appropriately and properly engineered to the relevant codes and standards. From the economics standpoints, the use of FRP materials in the piping system involving pipes and fittings diameter larger than 4 inch will provide substantial cost saving as opposed to other metallic materials. The cost saving will become more obvious with the increase in degree of piping system complexity